Reproductive performance and survival of Holstein and Holstein × Simmental crossbred cows - Knob D.A.* (2016)
© 2016, Springer Science+Business Media Dordrecht.Crossbreed dairy breeds, such as Holstein × dairy type of Simmental, have been generally used to improve fertility, udder health, and longevity of dairy herds. The aim was to compare the reproductive performance and survival of Holstein and Holstein × Simmental crossbred cows. Data from two farms were used as follows: one located in Bom Retiro, in the state of Santa Catarina, Brazil. and another in Carambeí, Paraná state. Information concerning birth, inseminations, and parity date were obtained from the management software of the farms, generating information regarding the calving interval, days between calving to first service, conception rate, and age at first calving. At one of the farms, calving was monitoring to quantify dystocia. Live weight as well as body condition score (BCS) of cows and information of culling were obtained to determine the survival rate. Data were analyzed by variance analysis and by logistic regression. Crossbred Holstein × Simmental cows had better reproductive performance than the Holstein cows, characterized by lower calving interval (381 vs. 445 days), higher conception rate (37.3 vs. 33.6 %), and shorter calving to first service interval (65 vs. 89 days). These results were related to a higher BCS in crossbred cows (3.63 vs. 2.94 points). Crossbred Holstein × Simmental cows had higher survival rate than Holstein cows on the second parity (83 vs. 92 %). No differences between genetic groups were observed (P > 0.05) for body weight and dystocia. In conclusion, Holstein × Simmental crossbred cows have better reproductive performance and higher survival rate than Holstein cows.